2001
DOI: 10.1002/1097-0215(200002)9999:9999<::aid-ijc1025>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Birth characteristics and breast cancer risk: A study among like‐sexed twins

Abstract: High birth weight has been proposed to increase the risk of breast cancer. Birth weight and gestational age are positively associated with intrauterine estrogen exposure, which may initiate the carcinogenic process in mammary gland tissue and determine mammary gland cell mass later in life. In the present case‐control study, we retrieved birth records for 96 female twin pairs where one twin had developed breast cancer. We used two control groups. In the external comparison, we used aged‐matched twins as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 13 publications
3
46
0
2
Order By: Relevance
“…Similar to several previous reports, we found a linear association between breast cancer and birth weight. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We also found an inverse association between birth weight and testicular cancer, which thereby strengthens the previous findings. [40][41][42][43][44][45][46] To our knowledge, only 2 smaller studies published to date have previously addressed the association between the overall risk of cancer and birth weight.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to several previous reports, we found a linear association between breast cancer and birth weight. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We also found an inverse association between birth weight and testicular cancer, which thereby strengthens the previous findings. [40][41][42][43][44][45][46] To our knowledge, only 2 smaller studies published to date have previously addressed the association between the overall risk of cancer and birth weight.…”
Section: Discussionsupporting
confidence: 88%
“…These studies show that women who were exposed to high foetal oestrogenic environment; that is, had a high birth weight or are twins, are at an increased risk of developing breast cancer (Braun et al, 1995;Michels et al, 1996;Sanderson et al, 1996;Weiss et al, 1997). At a particularly high risk are twins whose birth weight was high (Hubinette et al, 2001). A recent study also found that women exposed to the synthetic oestrogen diethylstilbestrol (DES) in utero are at an increased risk of developing breast cancer (Palmer et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…9 However, recent data suggest that high birth weight and long gestational age among twins are risk factors for breast cancer but whether these would modify the comparisons to the singleton population remains to be established. [11][12][13] The studies in families with multiple twins showed no excess risks of cancer among twins. In one family with 3 twins and an excess of breast cancer, the risk is unlikely to be related to twinning.…”
Section: Discussionmentioning
confidence: 99%